Enduring Themes?:: John Moss, the Arctic, and the Crisis in Representation - Saul, Joanne (Studies in Canadian Literature / Études en littérature canadienne, 1999)
Informed by the crisis of representation, John Moss discovers in Enduring Dreams: An Exploration of Arctic Landscape that he cannot write a book about the north without considering the long history of Arctic narrative and the textualization of Arctic space. Ostensibly a book about the Arctic, Enduring Dreams is actually a text about texts. Moss is drawn to the mythic nature of the north and its place in a Canadian consciousness; yet he recognizes that it is a space already textually overdetermined. His crossing of generic borders, his emphasis on the physicality of reading and writing, and his vast range of intertexts all serve to foreground his postmodern reflexive project. By insisting on the impossibility of narrating a "true" or "real" Arctic landscape, by refusing to historicize or contextualize within a material reality, and by resorting instead to the act of confession, Moss's text actually helps to strengthen the mythic nature of the north rather than challenge it. Like that of the explorers, adventurers, ethnographers, and artists he draws on, Moss's white, male, southern perspective creates a web of mystery around the north that effectively silences the land and people.